The stories about racism and health: the development of a framework for racism narratives in medical literature using a computational grounded theory approach - Caroline A. Figueroa; Erin Manalo-Pedro; Swetha Pola; Sajia Darwish; Pratik Sachdeva; Christian Guerrero; Claudia von Vacano; Maithili Jha; Fernando De Maio; Chris J. Kennedy (BMC, 2023)
Abstract Introduction The scientific study of racism as a root cause of health inequities has been hampered by the policies and practices of medical journals. Monitoring the discourse around racism and health inequities (i.e., racism narratives) in scientific publications is a critical aspect of understanding, confronting, and ultimately dismantling racism in medicine. A conceptual framework and multi-level construct is needed to evaluate the changes in the prevalence and composition of racism over time and across journals. Objective To develop a framework for classifying racism narratives in scientific medical journals. Methods We constructed an initial set of racism narratives based on an exploratory literature search. Using a computational grounded theory approach, we analyzed a targeted sample of 31 articles in four top medical journals which mentioned the word 'racism'. We compiled and evaluated 80 excerpts of text that illustrate racism narratives. Two coders grouped and ordered the excerpts, iteratively revising and refining racism narratives. Results We developed a qualitative framework of racism narratives, ordered on an anti-racism spectrum from impeding anti-racism to strong anti-racism, consisting of 4 broad categories and 12 granular modalities for classifying racism narratives. The broad narratives were "dismissal," "person-level," "societal," and "actionable." Granular modalities further specified how race-related health differences were related to racism (e.g., natural, aberrant, or structurally modifiable). We curated a "reference set" of example sentences to empirically ground each label. Conclusion We demonstrated racism narratives of dismissal, person-level, societal, and actionable explanations within influential medical articles. Our framework can help clinicians, researchers, and educators gain insight into which narratives have been used to describe the causes of racial and ethnic health inequities, and to evaluate medical literature more critically. This work is a first step towards monitoring racism narratives over time, which can more clearly expose the limits of how the medical community has come to understand the root causes of health inequities. This is a fundamental aspect of medicine's long-term trajectory towards racial justice and health equity.